Variabilidade da termoclina no Hemisfério Sul associada a eventos de zona de convergência do Atlântico Sul nas diferentes fases da oscilação de Madden-Julian - Pontes, Maissa Ludymilla Carvalho (2023)
The processes that occur in the ocean, both on the surface and at greater depths, are important for the global climate system, and the anomalies that occur in it are capable of influencing meteorological systems in different regions. The South American continent is bathed on its east coast by the South Atlantic Ocean, which plays an important role in modulating precipitation anomalies over South America. A better understanding of the relationship between temperature fluctuations in the ocean from the surface to high depths is important to better understand the weather and climate in this region, especially on the intraseasonal scale, which is widely analyzed in the Pacific, but little addressed in the Atlantic. Therefore, the objective of this work is to analyze the variability of the thermocline in the southern hemisphere on an intraseasonal scale and its relationship with the South Atlantic Convergence Zone. For this, 10 sub-regions were defined: four over the continent and six over the South Atlantic, and data from potential temperature reanalyses was used to calculate the average profile, boxplot and gradient for various ocean depths. From this, wavelet analyzes were performed. Daily precipitation data were also used to calculate the pentads, from which the fast Fourier transform was applied to filter out intraseasonal anomalies in the range of 20 to 120 days. These analyzes showed that the southernmost regions of the continent have greater amplitudes of intraseasonal anomalies in relation to the northernmost regions. The boxplot and gradient analyzes show that the tropical region has the thermocline with the lowest variation during the year, which can be observed throughout the period. The intraseasonal anomalies for the ocean showed that the regions centered on the subtropical belt and on the southwest ocean are the ones that showed the most significant signs of this variability. This variability occurs related to the regions where the thermocline presented a seasonal behavior, with alternation of depth during the year, which influences the mixed layer and increases the exchanges on the surface. With this, it is possible to observe that the regions further south of the continent and the ocean show more evident signs of intraseasonal variability than the regions further north.